2024
DOI: 10.1146/annurev-psych-040723-012736
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Attention and Memory

Nelson Cowan,
Chenye Bao,
Brittney M. Bishop-Chrzanowski
et al.

Abstract: The relation between attention and memory has long been deemed important for understanding cognition, and it was heavily researched even in the first experimental psychology laboratory by Wilhelm Wundt and his colleagues. Since then, the importance of the relation between attention and memory has been explored in myriad subdisciplines of psychology, and we incorporate a wide range of these diverse fields. Here, we examine some of the practical consequences of this relation and summarize work with various metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 197 publications
(227 reference statements)
0
6
0
Order By: Relevance
“…One of the most fundamental relations in human cognition is that between attention and memory (Cowan et al, in press), which has been investigated in studies of working memory (Cowan, 2019), long-term memory (Craik et al, 1996), intelligence (Conway et al, 2003), reading comprehension (Arrington et al, 2014), neuropsychology (Moscovitch & Umilta, 1990), childhood development (Forsberg et al, 2022), and adult aging (Greene et al, 2020). A core component of this relationship is the degree to which attention is needed to encode episodic memories—or memories for events occurring in a specific time and place (Tulving, 1983)—at both specific/detailed and general/gist levels of representation.…”
mentioning
confidence: 99%
“…One of the most fundamental relations in human cognition is that between attention and memory (Cowan et al, in press), which has been investigated in studies of working memory (Cowan, 2019), long-term memory (Craik et al, 1996), intelligence (Conway et al, 2003), reading comprehension (Arrington et al, 2014), neuropsychology (Moscovitch & Umilta, 1990), childhood development (Forsberg et al, 2022), and adult aging (Greene et al, 2020). A core component of this relationship is the degree to which attention is needed to encode episodic memories—or memories for events occurring in a specific time and place (Tulving, 1983)—at both specific/detailed and general/gist levels of representation.…”
mentioning
confidence: 99%
“…Our results replicate those of earlier findings in childhood development (Winsor et al, 2021), young adulthood (Wixted & Wells, 2017), and older adulthood (Colloff et al, 2017) documenting positive confidence–accuracy relations in LTM, albeit with variations in the strength of these relations across the lifespan (cf., Fandakova et al, 2013; Shing et al, 2009). Extending on these earlier studies, we found that similar confidence–accuracy relations arise in WM, the “gateway” through which new LTMs are formed (Forsberg, Guitard, Adams, et al, 2022; Forsberg, Guitard, & Cowan, 2021; Forsberg, Guitard, Greene, et al, 2022; Forsberg et al, 2023; Fukuda & Vogel, 2019; cf., Atkinson & Shiffrin, 1968; Cowan, 1988, 2019; Cowan et al, 2024). Moreover, the magnitude of the confidence–accuracy relation within an age group (i.e., the difference in recognition accuracy between lowest and highest confidence levels) was usually comparable in WM and in LTM, with rare exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…First, our definitions of WM and LTM are not intended to imply that these are separate memory systems. According to the embedded processes model (Cowan, 1988, 2019; Cowan et al, 2024), WM is an activated subset of LTM in which new LTM representations can be formed (cf., Oberauer, 2002). Due to its limited capacity, WM acts as an encoding bottleneck, constraining how much information individuals can later access in LTM (Forsberg, Guitard, & Cowan, 2021; Fukuda & Vogel, 2019; cf., Atkinson & Shiffrin, 1968).…”
Section: Terminology Used In the Present Studymentioning
confidence: 99%
“…This in turn may make these newly formed specific representations more immune to inference from subsequent events or to temporal decay. Indeed, attending to information during initial encoding is essential for establishing new, durable long-term memory representations (Cowan et al, 2024;Forsberg et al, 2021Forsberg et al, , 2022. Due to their more severely limited attentional resource capacity (Craik & Byrd, 1982;Hasher & Zacks, 1988), older adults may especially benefit from longer time to process information during encoding.…”
Section: Implications For Parallel Versus Serial Encoding Models Of S...mentioning
confidence: 99%
“…Differences in the speed of encoding each type of representation may underlie why, more so than younger adults, older adults often fail to retain specific details of their past experiences (Greene & Naveh-Benjamin, 2023a), in line with cognitive slowing theories of aging (Light, 1991;Myerson et al, 1990;Salthouse, 1996). Furthermore, representations that can be encoded more rapidly may require less sustained attention during encoding by being quickly off-loaded into passive (i.e., attention-freeing) storage (cf., Cowan, 1988Cowan, , 2019Cowan et al, 2014Cowan et al, , 2024Rhodes & Cowan, 2018).…”
mentioning
confidence: 99%